The Impact of ESG Reporting on Corporate Reputation and Crisis Communication Strategies in the Age of AI - Ács, Sarolta; Dér, Dezső Csaba; Santos-Rojos, Cristina; Michalec, Gabriela (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
In today’s climate of heightened corporate accountability and demand for sustainable business practices, ESG reporting has become a critical determinant of corporate reputation. As transparency expectations rise, regulatory frameworks such as the European Sustainability Reporting Standards (ESRS) require businesses to monitor and report ESG metrics accurately. To meet these demands, AI plays a transformative role, enabling real-time data collection and analysis that allows companies to monitor their environmental impacts, social initiatives, and governance practices with precision. This paper examines how AI-driven ESG reporting influences corporate reputation and crisis communication practices. By automating data collection, ensuring compliance, and providing real-time insights, AI empowers companies to proactively address sustainability challenges while strengthening stakeholder trust. Using a systematic literature review, this study synthesizes existing research on corporate reputation and crisis communication within the context of ESG reporting. Overall, the findings suggest that using AI-driven ESG reporting in corporate communication offers significant benefits for reputation and stakeholder engagement, however, crisis management practices are not yet well-defined in this area. By positioning AI as a strategic enabler in the ESG domain, this paper contributes to the evolving discourse on sustainable corporate governance and responsible investment, offering practical insights for executives, sustainability officers, and corporate communicators.